Implementation Of The Full Costing Method In Determining Logistics Delivery Rates - Wardokhi Wardokhi (CV. Ulil Albab Corp, 2024)
The company PT XYZ Ekspress operates in the field of delivery services for packages of goods and documents in small and large quantities. Because there are so many similar companies, a strategy is needed to survive in the current competitive situation. One of these strategies is in determining shipping rates. Determining competitive rates is done with more than estimates, but precise calculations are needed. The methods used include qualitative and quantitative approaches with data collection techniques in the form of documents and interviews. In determining shipping rates, PT XYZ Ekspress considers the shipment's distance and weight, which indirectly reflects cost considerations. The assumption is that the longer the distance and the heavier the goods sent, the higher the costs required. Determination of tariffs based on the Full Costing method uses costs as the basis for determining tariffs. In conclusion, costs are the basis for setting tariffs, so the determined selling price must be able to cover the costs incurred and obtain the desired profit, is correct. Tariff determination by PT Therefore, it is recommended that companies consider using the full costing method in the following years because this method places costs as the basis for setting rates so that the determined selling price can cover the costs incurred and obtain the desired profit.